Alien plant invasions in European woodlands. Issue 9 (6th August 2017) - Wagner, Viktoria; Chytrý, Milan; Jiménez‐Alfaro, Borja; Pergl, Jan; Hennekens, Stephan; Biurrun, Idoia; Knollová, Ilona; Berg, Christian; Vassilev, Kiril; Rodwell, John S.; Škvorc, Željko; Jandt, Ute; et al.
Abstract: Aim: Woodlands make up a third of European territory and carry out important ecosystem functions, yet a comprehensive overview of their invasion by alien plants has never been undertaken across this continent. Location: Europe. Methods: We extracted data from 251, 740 vegetation plots stored in the recently compiled European Vegetation Archive. After filtering (resulting in 83, 396 plots; 39 regions; 1970–2015 time period), we analysed the species pool and frequency of alien vascular plants with respect to geographic origin and life‐forms, and the levels of invasion across the European Nature Information System (EUNIS) woodland habitats. Results: We found a total of 386 alien plant species (comprising 7% of all recorded vascular plants). Aliens originating from outside of and from within Europe were almost equally represented in the species pool (192 vs. 181 species) but relative frequency was skewed towards the former group (77% vs. 22%) due, to some extent, to the frequent occurrence of Impatiens parviflora (21% frequency among alien plants). Phanerophytes were the most species‐rich life‐form (148 species) and had the highest representation in terms of relative frequency (39%) among aliens in the dataset. Apart from Europe (181 species), North America was the most important source of alien plants (109 species). At the local scale, temperate and boreal softwood riparian woodland (5%) and mire and mountain coniferous woodland (<1%) had the highest and lowest mean relative alien species richness (percentage of alien species per plot), respectively. Main conclusions: Our results indicate that European woodlands are prone to alien plant invasions especially when exposed to disturbance, fragmentation, alien propagule pressure and high soil nutrient levels. Given the persistence of these factors in the landscape, competitive alien plant species with a broad niche, including alien trees and shrubs, are likely to persist and spread further into European woodlands.